(untitled) (International Journal of Environmental Sciences, 2025)
Robotic technology is improving surgery by increasing dexterity, stability, and precision. Robots guide tools to the treatment location during image-guided surgeries using computed tomography and magnetic resonance imaging data. This calls for sensors to register the patient’s anatomy with the preoperative picture data, as well as novel algorithms and user interfaces for surgery planning. Through the use of remotely operated robots, minimally invasive procedures enable the surgeon to operate inside the patient’s body without creating significant incisions. Under these access restrictions, specialized mechanical designs and sensor technologies are required to maximize dexterity. Numerous surgical specializations can benefit from the use of robots. Robots guided by images can biopsy brain lesions during neurosurgery with little harm to surrounding tissue. Robots are frequently employed in orthopedic surgery to precisely shape the femur to fit replacement hip joints. Robotic systems are also under developed for closed-chest heart bypass, for microsurgical treatments in ophthalmology, and for surgical training and simulation. Despite the promising outcomes of the first clinical experience, concerns about safety, performance validation, high capital expenditures, and clinician acceptance still need to be addressed.